Sedentary lifestyle and its associated factors among adolescents from public and private schools of a Brazilian state capital - Flávia Miquetichuc Nogueira Nascente; Thiago Veiga Jardim; Maria do Rosário Gondim Peixoto; Carolina de Souza Carneiro; Karla Lorena Mendonça; Thaís Inácio Rolim Póvoa; Ana Luiza Lima Sousa; Weimar Kunz Sebba Barroso; Paulo César Brandão Veiga Jardim (BMC, 2016)
Abstract Background Adolescence is a transition stage between childhood and adulthood and is an important phase for the acquisition of future lifestyles, including the practice of physical activity (PA). The prevalence of sedentary lifestyle in adolescents is often high, creating the need for studies addressing the practice of PA and its associated factors for a better understanding of the phenomenon and possible interventions that would encourage positive changes. Methods Cross-sectional study of a representative sample of students aged 14-18 years enrolled in both public and private schools of a large Brazilian city to determine the level of physical activity (PA) and its associated factors. Sedentary lifestyle was measured by applying the International Physical Activity Questionnaire. The independent variables were gender, age, race, tobacco use and alcohol consumption in the past 30 days, socioeconomic status, body mass index, waist circumference and blood pressure. The crude prevalence ratio was used as a measure of association and was estimated from a Poisson regression. Results The sample consisted of 862 adolescents with a mean age of 15.4 ± 1.1 years. Females were predominant (52.8%), and the age between 14 and 15 years was the most frequent (52.2%). The majority of the group reported themselves as Caucasians (51.2%), belonging to socioeconomic class C (52.5%) and were attending to public schools (69.1%). The prevalence of sedentary lifestyle was 66.8% (95% confidence interval [CI]: 63.5-69.9), where values of 65.4% and 69.9% were observed among students from public and private schools, respectively (p = 0.196). Sedentary lifestyle was more frequent in females (78.0% vs 54.3%; p < 0.001). The factor directly associated with sedentary lifestyle was female gender both in public and private schools and the only independent variable related to sedentarism was also female gender. Conclusion The prevalence of sedentary lifestyle was extremely high in the population of adolescents studied both in public and private schools. Female sex was directly associated with sedentary lifestyle.